STOCK DIVIDENDS IN TRUST DISTRIBUTIONS. - Kerrigan, Harry D. (The Accounting Review, 1937)
A trust of corporate shares is often created under a will or other instrument in which it is directed that income of the trust is to go to a life tenant and that after this person's death the principal is to go to a remainder-man. If the trust instrument neglects to specify what is meant by income that is to go to the life tenant, doubtful items must be settled by the trustee. Among such doubtful items few have caused trustees more difficulty than stock dividends and the problem of allocating them between income and principal. The problem has driven trustees generally to seek the guidance of courts of law. As a result, the volume of litigation on the subject has steadily mounted. Because divergent judicial rulings exist between several states and varying applications of a given rule are made in the same state, trustees have readily submitted the problem for solution by courts at the expense of the trust fund rather than to decide the matter themselves and then become personally liable to suit by some dissatisfied party to the trust.